Unraveling gene content variation across eukaryotic giant viruses based on network analyses and host associations. Issue 2 (16th September 2021) - Sun, Tsu-Wang; Ku, Chuan
Abstract: The nucleocytoplasmic large DNA viruses (NCLDVs, phylum Nucleocytoviricota) infect vertebrates, invertebrates, algae, amoebae, and other unicellular organisms across supergroups of eukaryotes and in various ecosystems. The expanding collection of their genome sequences has revolutionized our view of virus genome size and coding capacity. Phylogenetic trees based on a few core genes are commonly used as a model to understand their evolution. However, the tree topology can differ between analyses, and the vast majority of encoded genes might not share a common evolutionary history. To explore the whole-genome variation and evolution of NCLDVs, we dissected their gene contents using clustering, network, and comparative analyses. Our updated core-gene tree served as a framework to classify NCLDVs into families and intrafamilial lineages, but networks of individual genomes and family pangenomes showed patterns of gene sharing that contradict with the tree topology, in particular at higher taxonomic levels. Clustering of NCLDV genomes revealed variable granularity and degrees of gene sharing within each family, which cannot be inferred from the tree. At the level of NCLDV families, a correlation exists between gene content variation, but not core-gene sequence divergence, and host supergroup diversity. In addition, there is significantly higher gene sharing between divergent viruses that infect similar host types. The identified shared genes would be a useful resource for further functional analyses of NCLDV–host interactions. Overall this study provides a comprehensive view of gene repertoire variation in NCLDVs at different taxonomic levels, as well as a novel approach to studying the extremely diverse giant virus genomes.